Enhancing performance, self-efficacy and well-being: A randomised controlled study in solution-focused business coaching - Réka Gerhát; Dorottya Ocsenás; Ákos Münnich (International Journal of Evidence Based Coaching and Mentoring)
This randomised controlled study examines the effectiveness of Solution-Focused Brief Coaching (SFBC) in an organisational setting involving 84 white-collar workers (Experimental Group, EG: 43, Waitlist Control Group, WCG: 41). Over three coaching sessions, the EG demonstrated significant improvements in performance, self-efficacy, well-being, and positive affect, while SFBC also effectively reduced negative affect. These outcomes were measured using both self-reported questionnaires and 360-degree performance evaluations. Notably, the positive effects were maintained four months after the coaching process. The study highlights SFBC as a powerful, time-efficient intervention for organisations, offering a practical approach to sustaining employee performance and well-being over time.